Neuropsychological features in patients with severe mental disorders and risk of violence: A prospective multicenter study in Italy. (July 2020) - Gobbi, Elena; Cotelli, Maria; Manenti, Rosa; Ferrari, Clarissa; Macis, Ambra; Bianconi, Giorgio; Candini, Valentina; Clerici, Massimo; Ferla, Maria Teresa; Iozzino, Laura; Vita, Antonio; de Girolamo, Giovanni
Highlights: Violent outpatients had difficulties in executive functions. Processing speed measure was sensitive to detecting cognitive deficits. Lower processing speed ability was associated to aggression against people. Abstract: In Severe Mental Disorders (SMDs) the most important cognitive deficits involve the Executive Functions (EFs). In this study we examined the association between EFs and aggressive behaviour in outpatients with SMDs. We included a total of 247 outpatients divided into two groups: 'cases', patients with a history of violence ( N =126) and 'non-violent' ( N =121). We compared their EFs score and then categorized the participants into four groups (Pathological Non-Violent comparison group; Non-Pathological Non-Violent comparison group; Pathological Violent cases and Non-Pathological Violent cases), based on the scores of a subtest assessing processing speed (i.e., Symbol-coding task) of the Brief Assessment of Cognition in Schizophrenia (BACS). We followed the 4 groups during a 1-year follow-up (FU) monitoring violent behaviour with the Modified Overt Aggression Scale (MOAS). According to the classification based on the BACS-Symbol Coding Task we found no statistically significant differences between subgroups in MOAS scores. We only found that the trend curve for PV was almost consistently over the other group curves in the MOAS 'aggression against people'. Our results suggested a worse performance in the violent compared to non-violent group in EFs. Despite this evidence, the score on the processing speed task was not associated with aggressive behaviour during FU.